1996
DOI: 10.1093/nar/24.24.4962
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an RNP Complex That Assembles on the Rous Sarcoma Virus Negative Regulator of Splicing Element

Abstract: We have characterized an RNP complex that assembles in nuclear extracts on the negative regulator of splicing (NRS) element from Rous sarcoma virus. While no complex was detected by native gel electrophoresis under conditions that supported spliceosome assembly, gel filtration revealed a specific ATP-independent complex that rapidly assembled on NRS RNA. No complexes were formed on non-specific RNA. Unlike the non-specific H complex, factors required for NRS complex assembly are limiting in nuclear extract. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Alternatively, with the full-length construct, enhancer factors bound to the 5Ј region might interact with and be preoccupied by factors bound to NRS3Ј (e.g., U11 or U1 snRNP), which might make them unavailable for interactions that result in enhancement of the dsx 3Ј splice site. This is supported by the in vitro formation of a large RNP complex on the NRS (the NRS complex) but not on NRS3Ј alone (5).…”
Section: Discussionmentioning
confidence: 94%
“…Alternatively, with the full-length construct, enhancer factors bound to the 5Ј region might interact with and be preoccupied by factors bound to NRS3Ј (e.g., U11 or U1 snRNP), which might make them unavailable for interactions that result in enhancement of the dsx 3Ј splice site. This is supported by the in vitro formation of a large RNP complex on the NRS (the NRS complex) but not on NRS3Ј alone (5).…”
Section: Discussionmentioning
confidence: 94%
“…There is also strong evidence that binding of the SR protein SF2/ASF is required for inhibition (12,19). These observations suggested that the NRS may be recognized as a 5Ј ss; in support of this proposal, we recently showed that the NRS assembles an ATP-independent complex, called NRS-C, that resembles the U1 E5Ј complex (7). NRS-C assembly requires ASF/SF2, U1 snRNP, and the U11 binding site, and based on a correlation between U11 binding and function (12), we speculated that NRS-C may represent a U11 E5Ј complex (8).…”
mentioning
confidence: 65%
“…pAd3Ј was made by cutting pAdHS with HindIII and BstEII to remove exon 1 and part of the intron, blunting, and religating. p3ZBB, used to generate NRS RNA, was described previously (7). pAdmutPyr, in which the pyrimidine tract is changed from TTTTTTTT to GTG ATCAC, was made by U.S.E.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using gel filtration chromatography, it was demonstrated that the NRS alone assembles into a complex that is indistinguishable from the early (E′) complex that forms on isolated 5′ splice sites (45,46). Furthermore, the complex appeared functionally relevant since there was a correlation between the sequence requirements for assembly in vitro and splicing inhibition in vivo, and assembly of the complex required SR proteins, the U1 binding site, and U1 snRNP (47).…”
Section: 33mentioning
confidence: 99%